2017
DOI: 10.1017/s0033291717002203
|View full text |Cite
|
Sign up to set email alerts
|

Auditory hallucinations, not necessarily a hallmark of psychotic disorder

Abstract: Auditory hallucinations (AH) are often considered a sign of a psychotic disorder. This is promoted by the DSM-5 category of Other Specified Schizophrenia Spectrum And Other Psychotic Disorder (OSSSOPD), the diagnostic criteria for which are fulfilled with the sole presence of persistent AH, in the absence of any other psychotic symptoms. And yet, persistent AH are not synonymous with having a psychotic disorder, and should therefore not be uncritically treated as such. Many people who seek treatment for persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 56 publications
1
25
0
6
Order By: Relevance
“…We report that AH and VH present in a significant proportion of PD and DLB cases, with both forms of hallucination being more prevalent in DLB. We found that VH have a higher prevalence than AH in both conditions, both occurring at rates much higher than those found in the general population (Ohayon, 2000; Waters et al, 2018). Of note were the wide variety of methods used to determine the presence of hallucinations.…”
Section: Discussionmentioning
confidence: 62%
“…We report that AH and VH present in a significant proportion of PD and DLB cases, with both forms of hallucination being more prevalent in DLB. We found that VH have a higher prevalence than AH in both conditions, both occurring at rates much higher than those found in the general population (Ohayon, 2000; Waters et al, 2018). Of note were the wide variety of methods used to determine the presence of hallucinations.…”
Section: Discussionmentioning
confidence: 62%
“…Cependant, les hallucinations ne sont pas l'apanage de la schizophrĂ©nie, elles sont au contraire rencontrĂ©es dans bien d'autres pathologies (Parkinson, Alzheimer, Ă©pilepsie) voire de façon isolĂ©e (47).…”
Section: J O U R N a L P R E -P R O O Funclassified
“…Some mental experiences, however, can occur on a continuum ranging from subthreshold levels in the general population to acute symptoms in clinical groups, and this observation has led to the exploration of symptom dimensions. In particular, the psychosis continuum theory (Johns and Van Os, 2001 ) suggests that the positive symptoms of psychosis (i.e., hallucinations and delusions) can exist at attenuated levels in the general population without being associated with distress or a loss of contact with reality that might warrant a need for treatment (Preti et al, 2014 ; Brett et al, 2015 ; Waters et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%